Higher Education Determinants and Graduate Employability: Evidence on Structural and Practical (mis)Match - Arbëresha Qerimi; Xhavit Rexhaj; Fidan Qerimi; Vrullim Buja (Emerging Science Journal, 2025)
Objective: The purpose of this research is to measure the impact of higher education factors on the employability of graduates in Kosovo and to measure the degree of mismatch between qualifications and labor market demand. Methods/Analysis: The research was conducted through a quantitative method, including a sample of 400 graduates, in the period 2019/20 to 2023/24. Data were collected through a structured electronic questionnaire, and the data were processed through SPSS. The reliability and validity of the instrument were tested through Cronbach's alpha and exploratory factor analysis. Correlation analysis, linear regression, ANOVA, the Tukey HSD test, and mismatch indices were used to present the results. Findings: The results show that the connection of study programs with the labor market is the factor with the highest impact on employability, while practical experience during studies has the lowest impact. The mismatch index shows that 63.5% of graduates work outside their field of study, 45.0% are over- or underqualified, and 49.5% have a lack of skills. The total mismatch index is 52.7%. Novelty/Improvement: This study provides empirical evidence on education-labor market mismatch, offering a solid basis for higher education reforms and public policies. It quantifies structural and practical mismatches shaping employability outcomes.